برنامج إدارة التعلم في تعليم اللغة العربية في إندونيسيا - Amrullah, M. Kholis; Hidayat, Nandang Sarip; Afnanda, Mihrab; Mukroji; Hawin Fitriyani (Postgraduate of IAIN Metro Lampung Indonesia, 2022)
Lecturers are required to understand the curriculum rules and course structure in order to get an integrative concept. The management of Arabic learning in the classroom becomes a place for the realization of the curriculum and learning plans that have been prepared. This study aims to review the approach to learning Arabic, classroom management in Arabic learning, challenges of classroom management, and improvement of classroom management problems in Arabic learning. The results of the study indicate that classroom management in learning Arabic as a foreign language is very dynamic and complex. This can be seen from the many factors involved, both from lecturers, students, and curriculum. Lecturer initiative in conducting research related to learning management is needed to improve the quality of the lecturers themselves and the quality of learning that will be developed. The manager must continue to develop the competence of lecturers in terms of education and professionalism to overcome errors in managing classroom behavior in teaching Arabic.